Features and management of men with pN1 cM0 prostate cancer after radical prostatectomy and lymphadenectomy: a systematic review of population-based evidence. Issue 1 (January 2022) - Laine, Charles; Gandaglia, Giorgio; Valerio, Massimo; Heidegger, Isabel; Tsaur, Igor; Olivier, Jonathan; Ceci, Francesco; van den Bergh, Roderick C.N.; Kretschmer, Alexander; Thibault, Constance; Chiu, Peter K.; Tilki, Derya; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Purpose of review: To investigate the features and optimal management of pN+ cM0 prostate cancer (PCa) according to registry-based studies. Recent findings: Up to 15% of PCa patients harbor lymph node invasion (pN+) at radical prostatectomy plus lymph node dissection. Nonetheless, the optimal management strategy in this setting is not well characterized. Summary: We performed a systematic review including n  = 13 studies. Management strategies comprised 13 536 men undergoing observation, 11 149 adjuvant androgen deprivation therapy (aADT), 7, 075 adjuvant radiotherapy (aRT) +aADT and 705 aRT. Baseline features showed aggressive PCa in the majority of men. At a median follow-up ranging 48–134months, Cancer-related death was 5% and overall-mortality 16.6%. aADT and aRT alone had no cancer-specific survival or overall survival advantages over observation only and over not performing aRT, respectively. aADT plus aRT yielded a survival benefit compared to observation and aADT, which in one study, were limited to certain intermediate-risk categories. Age, Gleason, Charlson score, positive surgical margins, pathological stage, and positive nodes number, but not prostate specific antigen, were most relevant prognostic factors. Our work further confirmed pN+ PCa is a multifaceted disease and will help future research in defining its optimal management based on different risk categories to maximize survival and patient's quality of life.